2020
DOI: 10.1002/nafm.10519
|View full text |Cite
|
Sign up to set email alerts
|

Limestone Remediation of an Acidic Stream Creates a Microchemical Batch Mark for Brook Trout within an Appalachian Watershed

Abstract: The addition of limestone sand directly to streams is an effective method for treating chemical and biological issues associated with acid precipitation, a common concern in many Appalachian watersheds. The unique water chemistry created by limestone remediation potentially creates a "mark" in fish hard parts (e.g., otoliths and fin rays) that can be used to identify fish from remediated habitats, even after fish disperse into the surrounding riverscape. We tested whether elevated concentrations of calcium fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Considerable effort has been allotted to mitigate current (acid remediation) and impending threats (climate change) to the brook trout metapopulation of the Shavers Fork watershed while taking a riverscape approach. Sources have been restored through acid remediation (Petty & Thorne 2005; McClurg et al 2007; Huntsman et al 2020), culverts replaced to re‐connect headwater sources with the main stem corridor (Wood et al 2018), and augmentation of the main stem habitat matrix to improve conditions for brook trout use (Merriam & Petty 2019; Trego et al 2019). We have shown that brook trout positively responded to main stem habitat augmentation with increased occupancy of this supplementary corridor post‐restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable effort has been allotted to mitigate current (acid remediation) and impending threats (climate change) to the brook trout metapopulation of the Shavers Fork watershed while taking a riverscape approach. Sources have been restored through acid remediation (Petty & Thorne 2005; McClurg et al 2007; Huntsman et al 2020), culverts replaced to re‐connect headwater sources with the main stem corridor (Wood et al 2018), and augmentation of the main stem habitat matrix to improve conditions for brook trout use (Merriam & Petty 2019; Trego et al 2019). We have shown that brook trout positively responded to main stem habitat augmentation with increased occupancy of this supplementary corridor post‐restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying bedrock geology and other landscape features (e.g. tributary confluences, beaver ponds) have created a high degree of variability in water quality, habitat, and biological characteristic throughout the riverscape (Petty et al 2001, 2005, 2012; Petty & Thorne 2005; Huntsman et al 2016, 2020; Merriam et al 2017; Merriam & Petty 2019; Trego et al 2019).…”
Section: Methodsmentioning
confidence: 99%